ACL and differentiability of open discrete ring (p,Q) -mappings - R. R. Salimov; E. A. Sevost’yanov (Математичні Студії)
We study the so-called (p,Q) -mappings which naturally generalize quasiregular mappings. It is proved that open discrete ring (p,Q) -mappings are differentiable almost everywhere as p>n−1 and locally integrable Q. Furthermore, we prove that open discrete (p,Q) -mappings belong to the class ACL in R n and f∈W 1,1 loc the same conditions on p and Q.